A new species of the genus Cryptocanthon from Peru (Coleoptera: Scarabaeidae: Scarabaeinae) - Giraldo-Mendoza, Alfredo Edgardo (Instituto de Ecología, A.C., 2022)
A new brachypterous species of Scarabaeinae, Cryptocanthon iskaypachak sp. nov. is described, discussed and illustrated based on specimens collected in Cajamarca department. The new species is the third of the genus Cryptocanthon recorded from Peru.